بنية التعبير في اللغة العربية بين التعليم والتدريس (مجلة الواحات للبحوث والدراسات, 2020)
The Activity Of Expression Is One Of The Most Prominent Of What The Teacher Stands In Teaching Arabic, And Its Sciences. There Is No Doubt That What Distinguishes This Technique Or Activity Is That It Is The Entrance To The Knowledge Of The Language And Its Sciences. In This Regard, We Consider The Expression Structure In Arabic The Structure Of The Crossroads Of Concepts Overlap, And Different Slightly, But We Can Put The Expression Structure, And The Justification For Research Lies In The Search For That Structure Of Education And Teaching, And The Fact That One Of Them Is More Comprehensive Than The Other In Determining The Specific Structure Of Expression, It Is Applied, And Will Be For The Beholder Various Cited In The Analysis; A Pillar Of Building The Concept Of Expression In Terms Of Structure And Conditions. Key - Words stylistic/structure/expression/arabica/éducation